2015
DOI: 10.1016/j.ceramint.2014.08.138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of infiltration temperature on the microstructure and oxidation behavior of SiC–ZrC ceramic coating on C/C composites prepared by reactive melt infiltration

Abstract: and SiO 2 , which covers the surface of the composites and retards the oxygen diffusion and the attack on the underlying C/C substrate. For SiC coated C/C composites, the large SiC particles formed on the surface of the composites are difficult to oxidize rapidly and so a continuous and dense SiO 2 layer cannot be formed in time to significantly hinder fast oxygen diffusion leading to the consequent severe oxidation of the C/C substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Up to now, some efforts have been focused on introducing ZrB 2 or ZrC phase in SiC-based coating to further improve its oxidation resistance, which is mainly attributed to the formation of stable compound silicate glass [10,11]. Dong et al prepared the SiC-ZrC coated C/C composites by reactive melt infiltration, whose mass gained 5.9 wt.% after oxidation at 1550 • C for 5 h [12]. Zhou et al fabricated the ZrB 2 -SiC coating by vapor silicon infiltration process, which could protect C/C substrate for more than 40 h [13].…”
Section: Introductionmentioning
confidence: 98%
“…Up to now, some efforts have been focused on introducing ZrB 2 or ZrC phase in SiC-based coating to further improve its oxidation resistance, which is mainly attributed to the formation of stable compound silicate glass [10,11]. Dong et al prepared the SiC-ZrC coated C/C composites by reactive melt infiltration, whose mass gained 5.9 wt.% after oxidation at 1550 • C for 5 h [12]. Zhou et al fabricated the ZrB 2 -SiC coating by vapor silicon infiltration process, which could protect C/C substrate for more than 40 h [13].…”
Section: Introductionmentioning
confidence: 98%
“…UHTCs based on several carbides and borides, possess a combination of high melting points, good thermal shock resistance and superior ablation resistance. Especially, zirconium carbide (ZrC) with high melting temperature (3540 • C), relatively low density (6.7 g/cm 3 ) and good chemical inertness, has been regarded as one of the most promising UHTCs [9,10]. Meanwhile, it has been largely reported that the addition of SiC can effectively improve the oxidation resistance of C/C composites [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced carbon and silicon carbide composites (C/C-SiC) have gained widespread attention in aerospace structural systems [1] and advanced friction systems [2] due to their superior mechanical properties under normal and high temperatures [3][4][5], oxidation and ablation resistance [6,7], and good friction and wear characteristics [8,9]. Developments in these applications will place higher requirements on these materials, and there is a need to find effective ways to improve their properties.…”
Section: Introductionmentioning
confidence: 99%